QSAR Modeling of a Novel Series of Methoxylated Chalcones as Antioxidant Agents Against Gram-Positive Bacteria Staphylococcus aureus - Neerja Shukla; Shashikant Verma (International Journal of Biochemistry and Biomolecule Research, 2025)
Background: Chalcones are aromatic ketones belonging to the flavonoid family. They are plant-based compounds and are widely found in nature. For centuries, these bioactive molecules have been utilized in various traditional medicines for the treatment of several ailments. Chalcones have antibacterial, antiviral, antimalarial, antifungal, antioxidant, and antileishmanial properties. They are also used to treat inflammation and cancer. Chalcones act as angiogenesis inhibitors, an important factor in cancer progression and metastasis. Method: QSAR analysis is done on a series of seventeen chalcones derivatives (1–16) using various physicochemical parameters. The study reveals that parameters, such as connectivity indices (χ5, χ6), ADME descriptors, molecular weight (MW), molar refractivity (MR), density (D), and LogP showed significant correlations with biological activity. The best results are obtained by performing multiple regression analyses with different models with strong R-squared values indicating robust predictive performance. Result: A combination of various descriptors, such as MR, MW, Pz, D, ADMET (LogS), and connectivity Indices (χ1–χ6) have been found to be best for the significant modeling of the anti-bacterial activity. QSAR model pIC50 = 3.374+ (–0.4484) χ5+ (0.5824) χ + (–0.2395) ADMET (LogS) optimized with empirical parameters with good statistical quality (R = 0.66, R2 = 0.44) was found to be the best model. Conclusion: The ADME solubility level reflects a molecule’s aqueous solubility, which can be predicted using molecular descriptors like the number of hydrogen bond donors and acceptors, dipole moment, rotatable bond count, and surface area. These factors are crucial in determining the solubility of the various organic compounds. Increased solubility has been shown to improve the antimicrobacterial activity. The positive sign of the connectivity indices implies that better better-designed drug can be obtained if there is an increase in the branching.
Keywords: ADME; Gram-positive bacteria; QSAR modeling; Staphylococcus aureus; methoxylated chalcones